Perlindungan Hukum Korban Kejahatan Siber dalam Tindak Pidana Perjudian Online di Indonesia - Sahat Maruli Tua Situmeang; Wahyudi Wahyudi; Musa Darwin Pane (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Online gambling in Indonesia has become a massive cybercrime, with financial turnover reaching IDR 976.8 trillion during 2017–2025. Behind these figures lie individual and family victims suffering material and immaterial losses, yet they are often positioned as offenders rather than protected parties. This study aims to analyze the legal framework for protecting online gambling victims, identify juridical and factual constraints in its implementation, and formulate an ideal protection model. The research employs a normative juridical method with statutory, case, and conceptual approaches. The findings indicate that Indonesian positive law does not recognize online gambling players as